Inovasi Sistem Informasi Pendaftaran Pasien Dengan Scanner Kib Dan Mesin Antrian Elektronik - Moh. Maulana (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2019)
Registration system at the Banjarsengon Community Health Center is still done manually starting from calling the queue number to the making of the MNH. Such a system would cause the patient registration process to be ineffective in terms of time while in the manufacture of MNH using paper material, it would not be durable or could be said to be damaged so that the writing could not be read. In addition, in looking for data on old patient visits, officers must search individual patients' names in the thick registration book. The purpose of this study is that all of the problems previously described can be resolved. The technology used in making the KIB scanner and the queue number uses RFID and sevent segment which is controlled by an Arduino microcontroller. Making the patient registration information system application using Microsoft Visual Studio 17. The results of this study are the patient registration information system with the MNH scanner and electronic queuing machine that can facilitate the registration officer in serving patients.